The Broadcasting Services Act (2001): an instrument for the development of community broadcasting in Zimbabwe?:Paper presented at SACOMM conference held from 28 to 30 September 2015 at AFDA Cape Town Campus - Ndawana, Tariro (Midlands State University, 2015)
At its invention radio was not taken seriously and many governments were reluctant to finance its development. However the scenario changed when the potential of radio was realised and governments began to regulate it. Zimbabwe does not comply with the African Charter on Broadcasting as it does not have Community radio. The study analyses the Act and carries out institutional analysis of CRIs. The study established that community radio initiatives in Zimbabwe are not licenced but are registered with the Ministry of Media, Information and Broadcasting Services. The country has over twenty CRIs and these are based in both urban and rural areas and their funding mainly comes from donors while most personnel at the stations are volunteers. The most vibrant of these CRIs operate in the capital city Harare and Bulawayo. Lack of licencing resulted in them broadcasting through the internet, messages over mobile phones as well as recording, distribution and playing radio programmes using compact discs. Since this is not real transmission some audiences do not get immediate information as in ‘real’ radio. There is need for the government to licence community broadcasters so that Zimbabweans have access to alternative radio.